TABUIK: WARISAN BUDAYA TAKBENDA DARI PARIAMAN - Wahyuni, Riya (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
This study discusses a traditional ceremony is a Hoyak Tabuik. A tradition that is always held every time the month of Muharram or the Hijri New Year from the city of Pariaman, West Sumatra. The Tabuik ceremony is held to see a flashback of the death of one of the grandsons of the Prophet Muhammad SAW, namely Husein bin Ali during the Battle of Karbala in fighting for Islam in 61 Hijriah by the army of Yazid bin Muawwiyah (680 AD/61 H). The time span used for the Tabuik event is 1-10 Muharram combined with Minangkabau traditional rituals. This study uses a qualitative descriptive analysis method with a literature study mode or library research related to local wisdom of the Pariaman region. The results of this study are expected to further introduce the hereditary tradition of Hoyak Tabuik to the wider community, the values obtained in this tradition are cooperation, solidarity, history and the strong relationship between religion and cultural tradition.